Intention of Junior High School Students towards Secondary Vocational Education and its Determinants in Rural China - Bin, Huang; CaiqunXu (Voprosy obrazovaniya / Educational Studies Moscow, 2013)
Huang Bin, Ph.D. in Philosophy, Deputy Director of the Center for Public Purpose Financing Research, Nanjing University of Finance and Economics, Jiangsu, China. Email: James7526@hotmail.com Address: 128 Railway N St, Gulou, Nanjing, Jiangsu, China, 210003. Xu Caiqun, Master’s degree, Finance and Taxation Institute, Nanjing University of Finance and Economics, Jiangsu, China. Email: xcqzy518@sina.com Address: 128 Railway N St, Gulou, Nanjing, Jiangsu, China, 210003. The paper investigates empirically the intention of Chinese rural students for the Secondary Vocational Education (SVE) and its determinants by using the survey data of Zhejiang, Anhui and Shanxi provinces collected in 2010. Results show that Chinese rural students nowadays have a strong tendency to accept the Secondary General Education (SGE), but their intention for SVE is relatively low. A list of variables is found to influence junior students’ intention in analysis of multinominal logistical regression. Students’ choice between SGE and SVE is mostly affected by personal academic performance, while family economic status exerts a significant effect on the choice between Employment and SVE. Whether junior students know about the government’s financial aid for rural SVE students or not won’t alter their intention. According to the survey results, it is strongly recommended to abolish the policy that aims to maintain the roughly equal enrollment between SGE and SVE. In addition, the central government should consider increasing the amount of financial aid for rural SVE students, especially for those in Central and Western China. The authors suggest that these measures will help students from low income families choose SVE and get professional education instead of entering the labor market too early.